PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA DAN KOMUNIKASI TERHADAP MOTIVASI KERJA PADA THE JAYAKARTA BALI BEACH RESORT RESIDENCE AND SPA DI KUTA BADUNG - Dwipayana, I Made Gede Angga; Sariyathi, Ni Ketut (E-Jurnal Manajemen, 2018)
The purpose of this study was to analyze the influence of transformational leadership, work discipline, and communication on employee work motivation. The research was conducted at The Jayakarta Bali Beach Resort, Residence & Spa. The population in this study were 300 permanent employees by taking samples amounting to 75 people determined by the method of proportional random sampling. Data were collected through interviews and questionnaires. Data were analyzed using multiple linear regression analysis technique.The result of this research is transformational leadership, work discipline, and communication have positive and significant effect to work motivation. Leaders of the company should encourage employees to be more creative dalm solve the problem of work, supervise and pay attention to employees in obey the rules set by the company and the leadership should improve communication with employees in solving work problems.